Is There a Role of 25-Hydroxy Vitamin D in the Pathogenesis of Mild and Moderate-to-Severe Endometriosis? - Tuten, Nevin; Acikgoz, Serdar; Mammadov, Zahid; Malik, Eduard; Tuten, Abdullah; Guralp, Onur (Gynecology Obstetrics & Reproductive Medicine, 2021)
Objective: To evaluate the possible associations between serum 25-hydroxy vitamin D levels and clinical and laboratory parameters in endometriosis. Study design: A total of 53 women with endometriosis and 37 women without endometriosis were evaluated in a, case-controlled study. The demographic features, clinical, and laboratory parameters of the two groups were compared. Results: The serum 25-hydroxy vitamin D levels were significantly decreased in both stage 1-2 and stage 3-4 groups compared to the controls (p<0.001 and p<0.001); although the difference between the stage 1-2 and stage 3-4 groups remained nonsignificant. The serum 25-hydroxy vitamin D levels had no correlation with the presence of infertility, deep infiltrating endometriosis, or Douglas pouch obliteration. The women who had bilateral endometrioma had significantly lower levels of 25-hydroxy vitamin D compared to the women with unilateral endometrioma (8.4±2.7 ng/mL vs 11.1±5.6 ng/mL, p=0.047). Mean serum 25-hydroxy vitamin D levels in women with and without dysmenorrhea were not significantly different from each other in the endometriosis and non-endometriosis subgroups. Serum 25-hydroxy vitamin D had no correlation with dysmenorrhea-VAS scores (r=-0.157, p=0.267). Conclusion: The mean serum 25-hydroxy vitamin D levels were significantly decreased in both mild and moderate to severe endometriosis groups compared to the controls. The serum 25-hydroxy vitamin D levels had no correlation with the presence of infertility, deep infiltrating endometriosis, or Douglas pouch obliteration. The women who had bilateral endometrioma had significantly lower levels of 25-hydroxy vitamin D compared to the women with unilateral endometrioma.